Pengaruh Penggunaan Ice Breaking Terhadap Motivasi Belajar Siswa Sekolah Dasar - Khurin In'Ratnasari; Mar’atus Sholihah; Dhevin M.Q Agus Puspita W (Auladuna : Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2023)
Ice Breaking is an activity carried out to break something that is hard or rigid. In the learning process, Ice Breaking means an activity carried out in the learning process that aims to melt a tense or boring atmosphere. The use of a variety of techniques and methods is very necessary in current learning. A teacher must be able to make all students feel comfortable during the learning process. It is intended that the objectives of learning can be achieved. Learning objectives can be achieved if students can understand what material is conveyed by the teacher. One important component in learning is how someone's learning interest in something. Mathematics is a subject that is generally considered a difficult subject to understand. The low interest in student learning in mathematics has become a common thing in society. Interest means someone's interest in doing something. So interest in learning is a student's interest in a particular matter or subject. This research uses quantitative methods with the type of research used, namely research Paired Sample T-Test. To determine the number of samples, researchers used techniques Purposive Sample that is, sampling must be based on certain characteristics, traits or characteristics which are the main characteristics of the population, the subjects taken must really be the subjects that contain the most characteristics found in the population. The results of this study say that there is an effect of usingIce Breaking Happy Feelings can Concentration or Attention in Learning and there is interest and motivation in learning